MEDAN MAKNA VERBA JATUH BAHASA DAYAK PANDU - Parisna, Lisa; Sukamto, Sukamto; Wartiningsih, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research focuses on one field of semantic study of the field meaning verbs fall in BDP. The general problem in this study was "Medan Meaning of Verbens Falling in Dayak Pandu Language". Subproblems in this study, namely how the components of meaning, word form, semantic function, and substitution of field sentences mean verbs fall in BDP. This study aims to describe the components of meaning, word form, semantic function, and the substitution of the phrase field meaning that the verb falls in BDP. The method used in this research is descriptive method with qualitative research forms. The data in this study are vocabulary and sentences which contain the meaning field of the falling verb BDP. The source of the data in this study is BDP which is spoken by native speakers of BDP. The techniques used are fishing techniques and interviews. The data collection tool in this study is a list of pictures and questions, folklore, and recording tools. Based on the results of data analysis, it can be concluded that in BDP can be obtained data of 28 components of meaning. The form of the word has the basic words, the word additive, and the word rephrase. Semantic functions have functions for humans, animals, plants, solid objects, and liquids. Substitution of sentences can be grouped according to the semantic characteristics of the subject, the number, origin of the fall, distance to fall, cause, level of pain, falling position, place of fall, and intentionality.Keywords: Meaning field, falling verb BDP